Gastro-retentive drug delivery systems and their in vivo success: A recent update - Mandal, Uttam Kumar; Chatterjee, Bappaditya; Senjoti, Faria Gias (Elsevier, 2016)
Gastro-retentive drug delivery system (GRDDS) has gained immense popularity in the field of oral drug delivery recently. It is a widely employed approach to retain the dosage form in the stomach for an extended period of time and release the drug slowly that can address many challenges associated with conventional oral delivery, including poor bioavailability. Different innovative approaches like magnetic field assisted gastro-retention, plug type swelling system, muco-adhesion technique, floating system with or without effervescence are being applied to fabricate GRDDS. Apart from in vitro characterization, successful GRDDS development demands well designed in vivo study to establish enhanced gastro-retention and prolonged drug release. Gama scintigraphy and MRI are popular techniques to evaluate in vivo gastric residence time. However, checking of their overall in-vivo efficacy still remains a major challenge for this kind of dosage form, especially in small animals like mice or rat. Reported in vivo studies with beagle dogs, rabbits, and human subjects are only a handful in spite of a large number of encouraging in vitro results. In spite of the many advantages, high subject variations in gastrointestinal physiological condition, effect of food, variable rate of gastric emptying time are the challenges which limit the number of available GRDDS in the market. This review article highlights the in vivo works of GRDDS carried out in the recent past, including their limitations and challenges need to overcome in the near future.